Morph-specific genetic and environmental variation in innate and acquired immune response in a color polymorphic raptor - Gangoso, Laura (2015)
Genetic color polymorphism is widespread in nature. There is an increasing interest in understanding the adaptive value of heritable color variation and trade-off resolution by differently colored individuals. Melanin-based pigmentation is often associated with variation in many different life history traits. These associations have recently been suggested to be the outcome of pleiotropic effects of the melanocortin system. Although pharmacological research supports that MC1R, a gene with a major role in vertebrate pigmentation, has important immunomodulatory effects, evidence regarding pleiotropy at MC1R in natural populations is still under debate. We experimentally assessed whether MC1R-based pigmentation covaries with both inflammatory and humoral immune responses in the color polymorphic Eleonora’s falcon. By means of a cross-fostering experiment, we disentangled potential genetic effects from environmental effects on the covariation between coloration and immunity. Variation in both immune responses was primarily due to genetic factors via the nestlings’ MC1R-related color genotype/phenotype, although environmental effects via the color morph of the foster father also had an influence. Overall, dark nestlings had lower immune responses than pale ones. The effect of the color morph of the foster father was also high, but in the opposite direction, and nestlings raised by dark eumelanic foster fathers had higher immune responses than those raised by pale foster fathers. Although we cannot completely discard alternative explanations, our results suggest that MC1R might influence immunity in this species. Morph-specific variation in immunity as well as pathogen pressure may therefore contribute to the long-term maintenance of genetic color polymorphism in natural populations.